Primary School Teachers’ Perceptions of the Level of Development of Low-Order Cognitive Skills Under the Content and Language Integrated Learning Approach - Campillo-Ferrer, José-María; Miralles-Martínez, Pedro (Frontiers in Education, 2022)
Content and Language Integrated Learning (CLIL) has become widespread in many countries around the world in an effort to improve learners' communicative competence in a foreign language (FL) and content acquisition in non-language areas (NLA). A successful CLIL programme must integrate the 4Cs, i.e., content, communication, cognition and culture. In this study, we focus on the synergies of developing thinking skills by combining language, content and cognition. Specifically, the aim of this study is to examine CLIL teachers' development of low-order cognitive skills (LOTS) in the subjects of Science and Social Science in the first two years of primary education in the Region of Murcia, Spain. For this purpose, we use a mixed method that combines qualitative and quantitative techniques to test the extent to which LOTS are developed within this integrated approach. The results show that most of the cognitive processes promoted by CLIL teachers are those related to fostering understanding among pupils, which sheds light on the strengths and weaknesses of these programmes and on a wide range of related factors on which further reviews are needed.